LE CONTREFACTUEL : ENTRE VISÉE DE DISCOURS, VISÉE PHRASTIQUE ET INCIDENCE - SOLIMAN, Luciana T. (Studia Universitatis Babeș-Bolyai Philologia, 2019)
The Counterfactual: Between Intended Message, Sentence Projection and Incidence. Within the framework of the cognitive principles which lie at the centre of the French system of the conditional, the aim here is to attempt to explain the function of the conjunction si by identifying some of the features it has in common with the Italian se. The expression of the counterfactual by means of the double imperfetto in the main and subordinate clause, or by means of the single imperfetto in the subordinate clause, is not simply due to the decline of the congiuntivo, but also to the morpheme that introduces a conditional idea which has been simplified and renewed by a process of levelling. From a psychomechanical perspective, we have explored the idea of hypothesis that the speech act presents from the start (Guillaume 1973; Joly and Roulland 1980; Hirtle 1994) in terms of «visée de discours» (the intended message) and «visée phrastique» (that is sentence projection), in view of the fact that the enunciation situation conditions the elaboration of the sentence upon the level of incidence (Lorian 1964; Moignet 1974; Skrélina 1980). Moreover, the study of a number of counterfactual clauses in Italian, taken from a contemporary literary genre which makes a legitimate use of these (Ammaniti 2001, 2006) has made it possible to verify the importance of the sociolinguistic dimension of substandard Italian by means of the process of semantic(-syntactic) revelation brought about by translation into French. REZUMAT. Construcția contrafactuală: între intenția mesajului, proiecția expresiei și incidență. Din perspectiva principiilor cognitive ce stau la baza sistemului francez al structurilor condiționale, scopul nostru este acela de a încerca să explicăm funcția conjuncției si prin identificarea unor trăsături comune între aceasta și italianul se. Exprimarea contrafactualului cu ajutorul dublului imperfetto în propozițiile principală și subordonată, sau cu ajutorul unui singur imperfetto în propoziția subordonată, nu se datorează pur și simplu unui declin al modului congiuntivo, ci și morfemului ce introduce o idee condițională simplificată și reînnoită printr-un proces de uniformizare. Dintr-o perspectivă psihomecanică, am analizat ideea de ipoteză pe care actul de vorbire o propune de la început (Guillaume 1973; Joly and Roulland 1980; Hirtle 1994) în termeni ca «visée de discours» (mesaj intenționat) și «visée phrastique» (sau propoziție proiectată), ținând cont de faptul că situația enunțării condiționează elaborarea propoziției de nivelul de incidență (Lorian 1964; Moignet 1974; Skrélina 1980). Mai mult decât atât, analiza unui număr de propoziții contrafactuale în italiană, preluate dintr-un gen literar contemporan ce le legitimează (Ammaniti 2001, 2006), a facilitat demonstrarea importanței dimensiunii sociolingvistice a limbii italiene neliterare printr-un proces de evidențiere semantică(-sintactică) prilejuită de traducerea în franceză. Cuvinte cheie: ipoteză, contrafactual, propoziție, intenționalitate, incidență, franceză, italiană.